Exploring the Students’ Inhibition in English Speaking Skill - Andeas, Andeas; Sudarsono, Sudarsono; Surmiyati, Surmiyati; Bunau, Eusabinus; Sumarni, Sumarni (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
This research focused on the students’ inhibition in English-speaking. This research aimed to describe the inhibiting factors faced by the students of Year-10 of MA Khulafaur Rasyidin in speaking English and to identify the strategies used by the teacher to reduce the inhibition. The type of research was descriptive. The tools to collect the data were questionnaires, observation, and interviews. The findings from the questionnaire reveal that self-confidence was the dominant inhibiting factor of affective that caused the inhibition of the student. Meanwhile, the dominant factor of cognitive that caused the inhibition of the students was pronunciation, grammar, and vocabulary together. The strategies used by the teacher were creating an anxiety-free and friendly environment, speaking slowly, giving appropriate feedback, using group work and discussion activities, encouraging the students to speak, reminding the students not to worry to make mistakes in speaking, and giving more opportunities for the students to speak.